Narrative, identity and ethics in postcolonial Kenya: the Young Women's Christian Association - Higgs, Eleanor Tiplady (Bloomsbury Studies in Religion, Gender, and Sexuality, 2021)
Introduction: narrative, memory, and history -- 1. 'Controversial faith issues' at the YWCA -- 2. Resisting imperialisms: Christianity, international development, and colonial women's movements -- 3. African, Christian, feminist? Negotiating sexual and reproductive ethics -- 4. 'We are Christians': the narrative construction of YWCA identity -- 5. Living 'fulfilled lives': ordinary theological ethics -- Conclusion: towards a feminist theory of ordinary theological ethics.